2010
DOI: 10.1002/mde.1497
|View full text |Cite
|
Sign up to set email alerts
|

Individual efficiency and club performance: a panel analysis of professional baseball

Abstract: This paper investigates whether players' individual- and club-level efficiency has substantial impact on club performance in the Chinese Professional Baseball League (CPBL). Using data from 1990 to 2000, and a stochastic frontier model, we propose a different way to measure club-level efficiency. Our empirical results indicate that club-level efficiency is crucial to club performance, measured by the winning percentage. Although the literature shows that some inefficient clubs with abundant resources are still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Other examples of the production function approach include Hadley et al (2000) for National Football League (NFL) teams, Kahane (2005) for National Hockey League teams, Barros and Leach (2007) for English Premier League teams. Jane et al (2010) analyze the effect of individual efficiency on club performance using data from professional baseball and show that the club level efficiency -accumulation of individual technical efficiencies-has an impact on club performance. Similarly, Teramoto and Cross (2010) examine the contributions of efficiency and related factors to winning games in both regular season and the playoffs in NBA.…”
Section: An Overview Of the Literaturementioning
confidence: 99%
“…Other examples of the production function approach include Hadley et al (2000) for National Football League (NFL) teams, Kahane (2005) for National Hockey League teams, Barros and Leach (2007) for English Premier League teams. Jane et al (2010) analyze the effect of individual efficiency on club performance using data from professional baseball and show that the club level efficiency -accumulation of individual technical efficiencies-has an impact on club performance. Similarly, Teramoto and Cross (2010) examine the contributions of efficiency and related factors to winning games in both regular season and the playoffs in NBA.…”
Section: An Overview Of the Literaturementioning
confidence: 99%
“…Their results showed that this salary increased from 6.19 million US dollars in 1985 to 38.67 million US dollars, with a 10.7% yearly average increase in salary. Jane et al (2010) adopted a stochastic frontier model to measure the correlation of the individual efficiency of baseball players against club performance. Studies found that winning percentages were related to runs scored, safety hits and home runs, rather than bases on balls and stolen bases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The next paper in this issue by Chang (2018) examines the demand for attendance at Chinese Professional Baseball League (CPBL) games in Taiwan. Previously, scholars have examined the performance of players in the CPBL (Jane, Kong, & Wang, 2010), as well as attendance demand in the league (Chen, Lin, & Lin, 2012). Though there are a handful of such studies, Taiwan has generally been an under studied context in Asian sports economics, especially when compared to South Korea or Japan.…”
Section: Attendance Demand In Chinese Professional Baseball Leaguementioning
confidence: 99%